HOW TO IMPROVE THE CALCULATION OF MEAN ARTERIAL PRESSURE AT THE BRACHIAL ARTERY LEVEL. (June 2018) - Furlanis, G.; Grillo, A.; Baldi, C.; Rovina, M.; Bilo, G.; Salvi, P.; Carretta, R.; Parati, G.
Abstract : Objective: Mean arterial pressure (MAP) is the time-averaged pressure through the cardiac cycle and may be calculated from brachial pressure values. Previous studies proposed thumb-rules, as adding 40% of pulse pressure to diastolic BP, to calculate MAP, but this approach is not unanimously accepted. We aimed to find the best way of calculating MAP by analyzing the brachial pressure wave. Design and method: We examined the pressure waveform obtained with brachial arterial tonometry (PulsePen, DiaTecne) in 1526 subjects from 3 cohorts (age 64.4 ± 18.2 years, 44.1% males), one from general population (n = 490, age 49.6 ± 12.7 years, 39.4% males), one of elderly patients (n = 284, age 87.6 ± 4.7 years, 25.4% males) and one of hypertensive patients (n = 752, age 59.2 ± 14.4 years, 54.3% males). Brachial pressure wave was calibrated with oscillometric systolic and diastolic brachial blood pressure measurement. The "real" MAP and the percentage of pulse pressure that needs to be added to diastolic blood pressure (PP%) to obtain the MAP were calculated from the time-averaged brachial pressure waveform. Results: The mean PP% in the pooled population was 42.2 ± 5.5% and was lower in the elderly cohort (40.8 ± 5.4%, p < 0.0001) than in the general population cohort (42.8 ± 6.0%) and in the hypertensives (42.2 ± 5.0%). PP% was higher in women (42.9 ± 5.6%) than in men (41.2 ± 5.1%, p < 0.0001), and was significantly correlated in multiple regression analysis with diastolic pressure (β=0.337, p < 0.0001), heart rate (β=0.091, p < 0.0001), while it was weakly related with age (β=-0.053, p = 0.05) and not related to systolic pressure. An equation to obtain an improved calculation of MAP in a single subject was derived from our data: PP% = 25.361 + 0.047*heart rate + 0.163*Diastolic pressure (+2.137 if female). Conclusions: Our data provide an estimate of the PP% required to be added to diastolic pressure to obtain the "real" MAP, which is 42.2% (with and SD of 5.5%). PP% presents a marked inter-individual variability, which discourages the use of a unique PP% for everyone. Our results offer the possibility to improve the calculation of MAP in the single subject by applying a formula derived from the analysis of the brachial waveforms in a large population.